Legitimising transgression: design and delivery of a science Work Integrated Learning program that draws on students' extant work in diverse, non-science fields. Issue 2 (23rd February 2020) - Rowland, Susan; Gannaway, Deanne; Pedwell, Rhianna; Adams, Peter; Evans, Robyn; Bonner, Hailey; Wong, Kai Sheng
ABSTRACT: Recent focus on graduate employability has exposed the inadequacies of work preparation for science students, who need an employability toolkit to navigate the modern work landscape. An established mechanism to develop students' employment awareness is Work Integrated Learning (WIL), but Australian mathematics and science students participate in fewer WIL activities than students in other disciplines. In this article, we present a conceptual discussion around the design of a non-traditional Bachelor of Science WIL program that transcends commonly held perceptions of WIL as primarily discipline-orientated and placement-based. This design dramatically expands the possibilities for WIL in science programs, enabling WIL participation for students unable to engage in a traditional science work placement. The program draws on and legitimises students' experiences in diverse non-science, part-time workplaces and extra-curricular activities; we term this 'transgressional learning'. Students engage in reflective and active learning opportunities designed to help them explore and articulate their skill sets in a manner that speaks to multiple future work settings. By drawing on students' extant work experiences, the program explicitly supports students to foreground and expand on broad skill sets acquired in extra-curricular settings. This article suggests a new conceptual approach and a path forward for large-scale WIL delivery in generalist science degrees. It draws on the reflections of the project team and student participants to outline the goals and design ethos of the program and reflect on the legitimacy of this transgressional program as a science WIL offering.